Tribocorrosion behaviour of biodiesel - Maleque, Md. Abdul; Abdulmumin, Adebisi Adetayo (Japanese Societies of Tribologists, 2014)
Biodiesel serves as the best alternative candidate to diesel fuel for diesel engines as a result of its ability to function as substitute to meet with the rising energy demand. It is considered because of its environmental friendly characteristics while giving almost the same functional properties like fossil fuels. This paper focuses on the tribo-corrosion behaviour of biodiesel followed by development of tribocorrosion model with the aim of understanding the combined effects of tribology and corrosion (synergism) for tribocomponent materials under biodiesel. A systematic review analysis was performed on the tribology, static corrosion for different biodiesel feedstock and factors affecting tribocorrosion system. A model has been developed to evaluate the corrosive wear of materials. It was found that synergism of wear and corrosion play an important role on the performance of biodiesel. Finally, it is expected to utilize the biodiesel with biocompatible engine component materials to enhance the reliability and performance.